Pengaruh Kemarau terhadap Pertumbuhan dan Produksi Tujuh Klon Kakao - Sugiatno Sugiatno; Ali Fitrah Hansyah; Rusdi Evizal; Sri Ramadiana (JURNAL AGROTROPIKA, 2022)
Long droughts and high rainfall as a result of climate change have an effect on reducing cocoa yields. This study aimed to study the effect of the 2019 drought on the growth and production of seven cocoa clones. The research was conducted from September 2019 to February 2020 in Cibinong Village, Way Ratai District, using a Randomized Block Design (RAK) with 3 replications and treatment of seven cocoa clones, namely BCL clones, BL 50, MCC 02, Sul 1, Sul 2, ICCRI 01, and ICCRI 03. The cacao plants used were 5 years old after side grafting using rootstocks of local varieties from seeds, with a monoculture planting system. The results showed that in 2019 Lampung Province experienced a long dry season with 7 dry months, namely from May to November, with a total rainfall of 1718 mm, and in August and September it did not rain at all. Clones had an effect on the number of cocoa leaves in November and February, but had no significant effect on the number of leaf flushes, number of flowers, number of pistils, and number of fruit. Long drought reduced leaf flush count, flower count, pistil number, and the number of small, medium, and large fruit. The long drought caused minor crop failures in the current year (in October) and major crop failures the following year (April). Key words : Cacao, clone, drought, growth, production